2012
DOI: 10.4067/s0717-95022012000300031
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Pattern of Chorionic Blood Vessels of Placenta and its Correlation with the Birth Weight of Neonate

Abstract: SUMMARY:Two hundred fresh full term placentae of normal pregnancies were collected from the department of Obstetrics and Gynaecology, RIMS, Ranchi, Jharkhand, India to observe the incidence of vascular pattern of chorionic blood vessels of placenta and to note the relationship between vascular pattern of placenta and the birth weight of neonate. Dye was injected into umbilical vessels under normal physiological pressure and diameter of chorionic blood vessels were taken at the centre and periphery. Two types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…In the present study, the mean fetal birth weight was 2167 grams in study group and in control group was 3010 grams .This indicates that the mean fetal birth weight is significantly lower by Renjana et al, [14] observed an evident relationship between the vascular pattern and fetal birth weight. It is higher in magistral pattern than the dispersal pattern.…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, the mean fetal birth weight was 2167 grams in study group and in control group was 3010 grams .This indicates that the mean fetal birth weight is significantly lower by Renjana et al, [14] observed an evident relationship between the vascular pattern and fetal birth weight. It is higher in magistral pattern than the dispersal pattern.…”
Section: Discussionsupporting
confidence: 52%
“…Most common Vascular pattern observed was mixed in 20 placentae, followed by magisterial in 19 placentae and least common pattern was dispersed, in 4 placentae. Gupta Anshu et al 23 and Verma Ranjana et al 2 have quoted only 2 types of vascular pattern (Disperse & Magisterial) in their study. While Lakshmi Devi C.K.…”
Section: Discussionmentioning
confidence: 95%
“…1 In intrauterine life, foetus depends upon the placenta for nutrition which function as its lungs, liver & kidney. 2 The wellbeing of the foetus depends on many factors, but healthy placenta is the single most common factor in producing a healthy baby. 3 The placenta acts as a unique organ in higher mammals which is attached to the uterus and the foetus via umbilical cord.…”
Section: Introductionmentioning
confidence: 99%